ADAPTATION OF “ART DECO” DESIGN STYLE USING DIGITAL PRINTING TECHNIQUE FOR DESIGNING HOME TEXTILE PRODUCTS - Mudgal, Sharvi; Singh, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the complex world of Art Deco, a well-known design movement that first appeared in the early 1900s. This study provides a comprehensive analysis of the key characteristics and influences that defined Art Deco, including geometric shapes, vibrant color palettes, exotic motifs, and diverse material choices. In the present study, researchers did experimental work on applying motifs inspired from Art Deco through digital printing. The researcher had adapted art deco motifs to create more stunning motifs of her own and applied them to home textile products by digital printing and designing the products was done using Ai (Adobe Illustrator) and Photoshop, one of the CAD software.